Effect of Liraglutide on Serum TSH Levels in Patients with NAFLD and its Underlying Mechanisms - JiaoJiao Ye; Jing Xu; WenJie Wen; Bin Huang (International Journal of Clinical Practice)
This study aimed to evaluate the effect of liraglutide on serum thyroid-stimulating hormone (TSH) levels in patients with type 2 diabetes mellitus (T2DM) and explore the underlying mechanisms via bioinformatics analysis. A total of 49 obese/overweight patients with T2DM received liraglutide during outpatient visits or hospitalization in the Department of Endocrinology. Meanwhile, the control group included 49 patients with T2DM but without nonalcoholic fatty liver disease (NAFLD) who were matched for age and sex (baseline from July 2016 to June 2021). Follow-up data on the last use of liraglutide were also retrieved. Age, sex, body mass index (BMI), and duration of diabetes were obtained from the participants’ records. All patients were tested for biochemical markers hemoglobin A1c (HbA1c), alanine transaminase, aspartate transaminase, free triiodothyronine, free thyroxine (FT4), and TSH at baseline and follow-up. After adjusting for all factors with a p-value < 0.05, BMI, HbA1c, LDL, FT4, and TSH were identified as significant independent risk factors for NAFLD in the univariate analysis. Following liraglutide therapy (average time 16 months), these patients had significantly lower BMI, HbA1c, and TSH but higher high-density lipoprotein (HDL) levels than those in the baseline data (all p < 0.05), and further subgroup analysis stratified by duration of liraglutide use showed that the test for time trends had statistical differences in BMI and TSH but not in HbA1c and HDL. After the therapy, the NAFLD and NASH groups showed significantly decreased TSH levels after liraglutide therapy compared with the corresponding baseline data. Furthermore, the expression of THRB, which encodes TRβ, was significantly decreased in the NAFLD group, which may explain the thyroid hormone resistance-like manifestation in the clinical findings. In conclusion, liraglutide improves hepatic thyroid hormone resistance in T2DM with NAFLD, and restoration of impaired TRβ expression in NAFLD is a potential mechanism involved in the process of liraglutide therapy.